Studying the Roles of Nonprofits, Government, and Business in Providing Activities and Services to Youth in the Phoenix Metropolitan Area. Issue 1 (May 2013) - Galaskiewicz, Joseph; Mayorova, Olga V.; Duckles, Beth M.
The article addresses the questions, What do children in urban areas do on Saturdays? What types of organizational resources do they have access to? Does this vary by social class? Using diary data on children's activities on Saturdays in the Phoenix-Mesa-Scottsdale metropolitan area, the authors describe the different types of venues (households, businesses, public space, associations, charities, congregations, and government/tribal agencies) that served different types of children. They find that the likelihood of using a charity or business rather than a government or tribal provider increased with family income. Also, the likelihood of using a congregation or a government facility rather than a business, charity, or household increased with being Hispanic. The authors discuss the implications for the urban division of labor on Saturdays and offer research questions that need further investigation.